Harnessing triaryloxonium ions for aryne generation - Smith, O; Hindson, MJ; Sreenithya, A; Tataru, V; Paton, RS; Burton, JW; Smith, MD (Springer Nature, 2023)
Arynes are highly reactive and versatile intermediates for the functionalization of aromatic rings that are often generated using strong bases or fluoride sources, which, in some cases, can limit functional group tolerance. Here we demonstrate that triaryloxonium ions can be transformed into arynes through treatment with solid potassium phosphate at room temperature. A substantial range of functional group-bearing arynes, including 4,5-pyrimidynes, may be generated and trapped using cycloaddition reactions with high yields. Other arynophiles including nitrones, alkenes and azides are compatible with these conditions. Quantum computation in conjunction with an intramolecular kinetic isotope study is consistent with an elimination, unimolecular, conjugate base-like mechanism of elimination to form the aryne. These investigations demonstrate that the oxonium ion is a powerful electron-withdrawing group and a particularly effective leaving group. We anticipate that this study will stimulate further investigations into the synthetic utility of aryl oxonium ions.